Monetary Policy Announcements, Information Schocks, and Exchange Rate Dynamics - Daniel Gründler; Eric Mayer; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
We study nominal exchange rate dynamics in the aftermath of U.S. monetary policy announcements. Using high-frequency interest rate and stock price movements around FOMC announcements, we distinguish between pure monetary policy shocks and information shocks, which are associated with new information contained in the announcements. Contractionary pure policy shocks give rise to a strong, but transitory, appreciation on impact. Information shocks also appreciate the exchange rate, but the effect builds up only slowly over time and is highly persistent. Thus, we conclude that although the short-run effects on the exchange rate are primarily due to pure policy shocks, the medium-run response is driven by information effects.
Keywords: E44; E52; E30; 330; central bank information; high-frequency identification; proxy VAR; exchange rate dynamics